Agricultural Sector Development Policy in Realizing Food Security in Kutai Kartanegara Regency - Budiyanto, Indra; Aqhsa, Nourial; Jamal, Muh (International Journal of Demos (IJD), 2024)
AbstractThis study aims to analyze the agricultural sector development policy in realizing food security in Kutai Kartanegara Regency. The research method used is secondary data analysis. Agricultural statistical data and local government policies are the main sources in conducting the analysis. The results and discussion of the study indicate that the vision and mission of agricultural development in Kutai Kartanegara Regency are very clear in supporting food security. Area-based agricultural development programs, the active role of local governments, and support for agricultural infrastructure are key factors in achieving this goal. The use of agricultural tools and machinery (Alsintan), adequate agricultural infrastructure development, coordination between regional apparatus organizations (OPD), and the adoption of modern agricultural technology and livelihood diversification have been discussed as relevant and important strategies. The implementation of these programs has been shown to increase agricultural productivity, farmer welfare, and food security in the region. A deep understanding of the various aspects of agricultural development and the challenges faced, as well as strategies to overcome them, provides a solid framework for the development of effective and sustainable policies and programs. Suggestions for improvement include a more detailed explanation of the relationships between subtopics and the presentation of more concrete examples or case studies to enrich the discussion.Keywords: Agriculture, Food Security, Kutai Kartanegara.